Fast Mapping Across Time: Memory Processes Support Children’s Retention of Learned Words - Vlach, Haley; Sandhofer, Catherine M. (Frontiers in Psychology, 2012)
Children's remarkable ability to map linguistic labels to objects in the world is referred to as fast mapping. The current study examined children's (N = 216) and adults’ (N = 54) retention of fast-mapped words over time (immediately, after a 1 week delay, and after a 1 month delay). The fast mapping literature often characterizes children's retention of words as consistently high across timescales. However, the current study demonstrates that learners forget word mappings at a rapid rate. Moreover, these patterns of forgetting parallel forgetting functions of domain general memory processes. Memory processes are critical to children's word learning and the role of one such process, forgetting, is discussed in detail—forgetting supports both word mapping and the generalization of words and categories.